ANALYSIS THE EFFECT OF JOB DESIGN AND COMPENSATION TOWARD EMPLOYEE SATISFACTION OF PT. BNI TBK, MANADO - Surina, Ni Wayan (Jurnal Berkala Ilmiah Efisiensi, 2015)
ABSTRACT The satisfaction of employees is the one important thing to maintain in the all of company in order to sustain their business activities. Â The purpose of this research is to know the effect of job design and compensation toward employee satisfaction particularly at PT BNI Manado, partially and simultaneously. 50 employees of PT. BNI Tbk had surveyed as the respondent in order to get the empirical data of this research. The result show that Job Design influence to the Employee Satisfaction positively, significantly, and partially influence and that Compensation partially influence positively and significantly the Employee Satisfaction. It is shown also that above Independent Variable (Job Design) and Compensation simultaneously influence positively and significantly Employee Satisfaction key words. Keywords: Job Design, Compensation, Employee Satisfaction.